The relationship between premature ejaculation and the timing of pre-adult circumcision - (:unkn) unknown (WILEY, 2021)
We aimed to investigate the relationship between premature ejaculation and the age when men had been circumcised before adulthood. A total of 2,768 sexually active male patients aged between 18 and 65 years were included in this study. A multicentre study was conducted prospectively with the participation of 20 centres. A survey consisting of 12 questions prepared by the researchers, as well as the validated Turkish versions of the five-item Premature Ejaculation Diagnostic Tool, was administered to all participants. The study included 1,603 participants who met the inclusion criteria. There was no significant difference in the Premature Ejaculation Diagnostic Tool and self-reported ejaculation time between the participants who had been circumcised at different ages during childhood. Remembering circumcision experience with fear or anxiety did not increase the risk of sexual dysfunction compared to the participants who described their experience with happiness or with no particular emotion. There was no significant difference in Premature Ejaculation Diagnostic Tool scores or the self-reported ejaculation time of the participants circumcised at different ages. The age of childhood circumcision, having a fearful or anxious circumcision experience, does not affect the risk of premature ejaculation in adult life.
Keywords: circumcision; erectile dysfunction; premature ejaculation; TURKISH VALIDATION; UNITED-STATES; PREVALENCE; AGE